PENINGKATAN PERILAKU ASERTIF MELALUI KEGIATAN PUBLIC SPEAKING PADA SISWA SMP AL-MUQODDASAH NGLUMPANG MLARAK PONOROGO UNTUK MEREDUKSI TINDAK BULLYING - Wijayanti, Dian Rahayu; Nugraha, Nurhadji; Sudarmiani, Sudarmiani (FKIP Unirow Tuban, 2020)
This study aims to determine the extent of increasing assertive behavior of SMP Al-Muqoddasah Ponorogo students through Public Speaking activities to help reduce bullying. This study uses descriptive qualitative methods to solve a problem or determine an action, for this reason it needs a number of information data collected in the form of words, pictures and not numbers. The technique used in the form of observation, interviews and documentation. Validity uses triangulation techniques with sources.The results showed that the Public Speaking activities at SMP Al-Muqoddasah Nglumpang Mlarak Ponorogo were able to help improve assertive behavior of some students so as to reduce the occurrence of bullying in the school environment, even though students were still found to be victims of bullying. This is due to the failure of students in self-concept, and low self-esteem due to low asretivity.